MANAJEMEN TALENTA DI PEMERINTAH DAERAH KOTA BEKASI - Muhamad Jihafan, Haykal; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2025)
The KASN report (2023) highlights low achievement in the career development aspect of Indonesia's State Civil Apparatus (ASN), with a score of only 33.5%. This reflects a lack of attention to talent management, including the absence of talent pools and succession plans in government agencies, affecting the optimal implementation of the merit system. The Bekasi City Government has attempted to implement talent management through Mayor's Regulation No. 12 of 2022, but challenges persist, especially in ensuring comprehensive implementation. For instance, there was a score of 0 in the availability of a succession plan, and issues like position trading have occurred. This study aims to describe the stages of talent management implementation in the Bekasi City Government and identify the factors influencing its execution. The theories applied in this research are Person-Organization Fit (Kristof, 1996), the talent management framework (Kartika, 2020), and factors influencing talent management (Sehatpour et al., 2020). The research uses a qualitative approach with a combination of purposive sampling and snowball sampling to select relevant subjects from the Bekasi City Personnel and Human Resources Agency (BKPSDM). The results indicate that while talent management stages in Bekasi City have begun, they have not been fully optimized or implemented comprehensively. Talent acquisition, development, and retention have been initiated but require further improvement, and talent placement has not been aligned with succession plans due to incomplete information systems. Factors influencing the implementation include cultural, managerial, human resources, and environmental aspects, as well as the commitment of leadership and the readiness of a talent management information system. The study recommends strengthening talent acquisition strategies, launching a cadre school program for career development, and ensuring talent placement aligns with a more structured succession plan.